Revealed comparative advantage and competitiveness of broiler meat products in Malaysia and selected exporting countries - Abdulaker Benalywa, Zineb; Ismail, Mohd Mansor; Shamsudin, Mad Nasir; Yusop, Zulkornain (Universiti Malaysia Sarawak, 2019)
In this paper, the level of competitiveness and comparative advantages of broiler meat products from Malaysia and selected counties have been analysed. The level of competitive advantage was measured using four different indices: RXA, RTA, ln RXA, and RC for a period from 2009 to 2017. For each index, the existence of a correlation between them has been investigated to ascertain which of the four chicken meat products stand out with a definite competitive advantage. This research establishes the presence of the international trade market share with products from the Malaysian broiler industry. The results found that, in Malaysia, only HS020712 (whole chickens and capons, frozen) showed an increase in competitiveness over the period 2012 to 2017